Comparative RNA-seq and functional assays identify L-arginine transporter SLC7A2 as a potential regulator of osteogenesis in maxillary sinus mucosal stem cells - Ren, Jing; Geng, Ningbo; Zhou, Tianren; Mo, Shiting; Zhang, Chi; Peng, Wei; Liao, Chunhui; Chen, Songling (Frontiers in Genetics, 2025)
BackgroundThe osteogenic differentiation of maxillary sinus mucosal stem cells (MSMSCs) plays a critical role in maxillary sinus floor elevation, yet its underlying regulatory mechanisms remain unclear. In addition, although both MSMSCs and palatal mesenchymal stem cells (PMSCs) may participate in bone regeneration, their osteogenic differentiation characteristics and molecular regulation differences have not been systematically analyzed. Therefore, the study aimed to characterize the transcriptional differences between MSMSCs and PMSCs during osteogenesis and identify the role of solute carrier family 7 member 2 (SLC7A2) in MSMSCs’ osteogenic differentiation.MethodsRNA sequencing (RNA-Seq) was conducted to compare gene expression profiles of MSMSCs and PMSCs at baseline (day 0) and 7, 14, and 21 days after osteogenic induction. Osteogenic differentiation was evaluated using Alkaline Phosphatase (ALP) staining, Alizarin Red S (ARS) staining, Western blotting, and quantitative polymerase chain reaction (qPCR) for the osteogenic markers osteocalcin (OCN), runt-related transcription factor 2 (RUNX2), and bone morphogenetic protein 2(BMP2). A lentiviral-based SLC7A2-silencing model was established in MSMSCs to silence SLC7A2 expression and thereby investigate its role in osteogenic differentiation.ResultsMSMSCs and PMSCs exhibited similar osteogenic gene expression patterns, but their underlying regulatory mechanisms differed. Notably, amino acid metabolism-related pathways were significantly enriched in MSMSCs during osteogenesis. SLC7A2 was identified as one of the top 10 differentially expressed genes (DEGs) common to MSMSCs at baseline (day 0) and 7, 14, and 21 days after osteogenic induction (FDR <0.05 and |log2FC| ≥2.0). Functional experiments further demonstrated that SLC7A2 knockdown in MSMSCs resulted in a significant decrease in ARS staining and ALP activity, and significantly suppressed the expression of OCN and RUNX2 compared to the control shEV group (P < 0.05, n = 3).ConclusionThe osteogenic differentiation of MSMSCs is tightly associated with amino acid metabolism.Notably, SLC7A2—an L-arginine transporter—is a gene required for the efficient osteogenic differentiation of MSMSCs. This study provides novel evidence to advance our understanding of the molecular mechanisms underlying stem cell osteogenic differentiation during maxillary sinus floor lifting surgery,and further suggests that SLC7A2 may serve as a potential target to enhance the efficacy of MSMSCs-based bone regeneration.